Invasive Mycobacterium abscessus Outbreak at a Pediatric Dental Clinic. (15th April 2021) - Singh, Jasjit; O'Donnell, Kathleen; Nieves, Delma J; Adler-Shohet, Felice C; Arrieta, Antonio C; Ashouri, Negar; Ahuja, Gurpreet; Cheung, Michele; Holmes, W Nathan; Huoh, Kevin; Tran, Lisa; Tran, M Tuan; et al.
Abstract: Background: Mycobacterium species, specifically M. abscessus and M. chelonae (MABs), are known to contaminate water systems and are uncommon causes of health care–associated infection, but morbidity can be significant and treatment complex. Methods: Odontogenic MAB infections occurred in patients following pulpotomy procedures at dental clinic A from 1 January to 6 September 2016. We identified confirmed and probable cases using culture data, imaging, pathology results, and surgical findings. Epidemiologic and clinical data including demographics, symptoms, laboratory findings, treatment regimens, and outcomes were extracted. Results: Of 1082 at-risk patients, 71 case patients (22 confirmed; 49 probable) were identified. Median age was 6 years. Median symptom onset was 85 days postpulpotomy. Pain and/or swelling on admission occurred in 79%. On imaging, 49 of 70 had abnormalities of the mandible or maxilla, 13 of 70 had lymphadenopathy, and 19 of 68 had pulmonary nodules. Seventy were hospitalized (average of 8.5 days). Intravenous antibiotics were administered to 32 cases for a median length of 137 days. Clofazimine was administered to 29 patients as part of their multidrug regimen. Antibiotic treatment was associated with many adverse effects. Treated children showed evidence of jaw healing with resolved/improving pulmonary nodules at 1-year follow-up. Conclusions: This is the largest outbreak of invasive MAB infections associated with a pediatric dental practice. While infections were indolent, patients suffered medical and surgical consequences of treatment, including permanent tooth loss. Identification of this outbreak led to a change in water standards for pediatric dental procedures in California. Enhanced national dental water quality standards are needed to prevent future outbreaks. Abstract : We describe 71 pediatric cases of invasive M. abscessus infections associated with a dental practice. While infections were indolent, patients suffered medical and surgical consequences. This led to a change in water standards for pediatric dental procedures in California.